2021
DOI: 10.1016/j.radonc.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Value-based radiotherapy: A new chapter of the ESTRO-HERO project

Abstract: Radiotherapy interventions are rapidly evolving and improving, holding promise for better patient outcomes, yet at the possible detriment of higher societal costs. The ESTRO-HERO value-based radiotherapy project aims to develop a framework defining and assessing the value of radiotherapy innovations, to support clinical implementation and equitable access, within a sustainable healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Previous studies focusing only on patient reported outcomes and/or HRQoL between the two treatment regimens in low-intermediate-risk PCa reported no substantial differences [3][4][5][6][7]. Overall, with moderate H-RT being clinically non-inferior to C-RT [15], significantly less costly than C-RT and without worse QALY, the results of our CEA show that H-RT is a dominant strategy Despite the high burden of PCa, economic evaluations are scarce [9]. To our knowledge, this is the first European study exploring the cost-effectiveness of H-RT compared to C-RT, based on longitudinal real-world data on costs and HRQoL from a clinical trial [8,10,11,13,14].…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Previous studies focusing only on patient reported outcomes and/or HRQoL between the two treatment regimens in low-intermediate-risk PCa reported no substantial differences [3][4][5][6][7]. Overall, with moderate H-RT being clinically non-inferior to C-RT [15], significantly less costly than C-RT and without worse QALY, the results of our CEA show that H-RT is a dominant strategy Despite the high burden of PCa, economic evaluations are scarce [9]. To our knowledge, this is the first European study exploring the cost-effectiveness of H-RT compared to C-RT, based on longitudinal real-world data on costs and HRQoL from a clinical trial [8,10,11,13,14].…”
Section: Discussionmentioning
confidence: 48%
“…Moderate H-RT stands as a strong recommendation for intermediate-risk PCa in the 2021 EAU-EANM-ESTRO-ESUR-SIOG guidelines [2], based on its comparable effectiveness to C-RT without increasing toxicity [1], nor altering patients' Quality of life (QoL) [3][4][5][6][7]. In addition, H-RT might be considered as a cost saving option [8] and improve availability of RT treatments, addressing supply shortages and disparities in access that have been observed in many European countries [9]. However, robust health economics evidence is needed to support the use of H-RT as a strategy yielding to improved patient reported outcomes, such as health-related QoL (HRQoL) per euro spent [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ESTRO has introduced the value-based health care (VBHC) project, an initiative addressing key issues including defining the outcomes supporting the implementation of new innovations (e.g. clinical, economic and patient-centred outcomes) as well as defining the level of value and evidence needed before implementation into daily practice [73] , [74] . The model presented here can be easily modified to account for any updates to guideline recommendations as new evidence emerge, or changes in the distribution of epidemiological data within the population.…”
Section: Discussionmentioning
confidence: 99%
“…Some initiatives have started to work towards correcting these marked geographical discrepancies, as illustrated in Fig. 3 [36][37][38][39][40]. Since research activity has a knock-on effect on the delivery of clinical radiotherapy (and other) services, this is a major challenge in providing equity of access to cancer care.…”
Section: Geographical Disparitiesmentioning
confidence: 99%